GAYA KOMUNITAS KARYAWAN UNTUK MENINGKATKAN KINERJA DAN DISIPLIN KERJA PADA PT NSP - Mochamad Fatchurrohman; Teguh Setiawan Wibowo; Priscadella Putri Christiyanti; Noneng R Sukatmadiredja; Shobikin (Ekomania, 2024)
This research aims to study and find out how employee communication styles at PT. NSP can contribute to improving work performance and discipline. In a competitive business environment, employee performance and a high level of work discipline are the keys to achieving company success and growth. The application of communication styles in the workplace has become an increasingly relevant concern for managers and human resources practitioners in efforts to create a positive corporate culture. Decision making, communication channels, and character. This researcher uses a post-positivism paradigm, and this research uses qualitative methods. The results of this qualitative method show that the communication style of employees at PT. NSP is The Relinguishing Style because they prefer collaboration with teams and deliberation so they can exchange thoughts, input or ideas with other team members. As well as wanting a conducive working atmosphere so that ASNs can work more calmly and quickly.